2017
DOI: 10.1089/lgbt.2016.0208
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Medicare Beneficiaries and Chronic Conditions: Exploring Fee-for-Service Claims Data

Abstract: Purpose: Data on the health and well-being of the transgender population are limited. However, using claims data we can identify transgender Medicare beneficiaries (TMBs) with high confidence. We seek to describe the TMB population and provide comparisons of chronic disease burden between TMBs and cisgender Medicare beneficiaries (CMBs), thus laying a foundation for national level TMB health disparity research. Methods: Using a previously validated claims algorithm based on ICD-9-CM codes relating to transsexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 36 publications
6
117
1
Order By: Relevance
“…This is consistent with recent findings that 71% of gender-minority Medicare beneficiaries were entitled to disability and experienced more disabilities compared with non-gender minority beneficiares. 4 These findings highlight the urgent need to understand both the causes of disability among TGNC people and the intersectional experiences of transgender people with disabilities in order to improve culturally competent care.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with recent findings that 71% of gender-minority Medicare beneficiaries were entitled to disability and experienced more disabilities compared with non-gender minority beneficiares. 4 These findings highlight the urgent need to understand both the causes of disability among TGNC people and the intersectional experiences of transgender people with disabilities in order to improve culturally competent care.…”
Section: Discussionmentioning
confidence: 98%
“…3 These population-level findings, although limited by small sample sizes, found fewer health disparities than studies using community and clinical samples, which documented high rates of psychological distress, HIV, sexually transmitted infections, disabilities, and risky health behaviors among transgender populations. 4 Second, this study evaluates transgender health in domains that have previously been unexamined in the literature. These gaps are due, in part, to the absence of gender identity measures in national health surveillance, 1 as well as inadequate funding for transgender-specific health research: between 1989 and 2011, NIH funded only 43 transgender-specific studies, most of which focused on HIV-related health issues.…”
Section: Introductionmentioning
confidence: 99%
“…Even for individuals who can afford HT OOP costs, these expenses should be considered in the context of an individual's overall medication regimen. Transgender Medicare beneficiaries more commonly have multiple chronic medical conditions than cisgender beneficiaries, 10 and they have more emergency department visits and hospitalizations. 26 These cost and access burdens may explain why nearly 1 in 10 transgender people has acquired HT through nonlicensed sources such as friends or online.…”
Section: Discussionmentioning
confidence: 99%
“…3 There has been no systematic examination of formulary coverage for hormone therapies and it is unknown whether and to what degree health plans for Medicare beneficiaries are providing coverage for these therapies for older transgender adults, a particularly vulnerable subgroup who may face several unique challenges, such as increased identity concealment in health care settings and difficulty identifying clinicians who can manage HT in the setting of medical comorbidities. [9][10][11][12] Accordingly, we examined Medicare prescription drug plan (PDP) formulary coverage and restrictions for those hormone therapies recommended in the 2009 and 2017 Endocrine Society treatment guidelines, 6,13 including out-of-pocket (OOP) costs associated with hormone therapies. We expect our findings to help provide a better understanding of the cost and access barriers faced by the transgender population.…”
Section: Introductionmentioning
confidence: 99%
“…20 Prior research using Medicare Fee-for-Service (FFS) claims data has identified a method to identify transgender beneficiaries receiving gender-affirming care and examine chronic disease burden and patterns of disparities among Medicare beneficiaries. 21,22 Identifying transgender patients in administrative data can be challenging because diagnosis codes only identify people who receive transgender-related medical care, not all patients of transgender experience. In addition, gender is not captured using the recommended two-step method of patient-reported sex assigned at birth and current gender identity.…”
Section: Introductionmentioning
confidence: 99%